PRODUCTION OF ACTIVATED CARBON OF PALMYRA PALM FRUIT SHELL (Borassus flabellifer Linn.) FROM KISAR ISLAND, SOUTHWEST MALUKU REGENCY FOR ADSORPTION OF METHYL RED DYE - Maromon, Ingrid Natasya Tritama; Utubira, Yeslia; Untailawan, Romelos (Program Studi Pendidikan Kimia, FKIP, Universitas Pattimura (Chemistry Education Study Program, Faculty of Teacher Training and Educational Sciences, Pattimura University), 2023)
Palmyra palm is a species of palmae that grows a lot on Kisar Island where all parts of the plant can be utilized. However, the palmyra palm fruit shell has not been used and that is only thrown away. In this study, palmyra palm fruit shell were made as activated carbon and were characterized using XRD to determine the crystallinity properties of the palmyra palm fruit shell activated carbon and adsorption test was carried out to determine the capacity and efficiency of activated carbon adsorption to methyl red dye. The production of palmyra palm fruit shell activated carbon is carried out through the carbonization stage at 300°C for 1 hour, and followed by chemical activation using H3PO4 10% solution for 24 hours. The results of the analysis using XRD showed that the activated carbon of the palmyra palm fruit shell formed peaks with the highest intensity at diffraction angles of 2θ = 26.5241° and 27.6274° with d-spacing values ​​(Å) = 3.36059 and 3.22884, which are characteristic peaks of carbon and are amorphous. The adsorption of methyl red 20 ppm use batch method, with various contact times of 5, 10, 15, 20, 25, and 30 minutes. The results of showed that on 15 minutes was the optimal time, with 0.25 gram mass of the adsorbent and the adsorption capacity and adsorption efficiency was 0.87 mg/g and 44.3%, respectively.